Low PAPP-A Levels and Pregnancy Outcomes [21J]. (May 2018) - Shand, Muhammed F.; Gimovsky, Alexis; Macri, Charles
Abstract : INTRODUCTION: Pregnancy-associated plasma protein A (PAPP-A) is associated with adverse pregnancy outcomes: preterm birth, growth restriction, stillbirth and preeclampsia. Because PAPP-A affects placental function, it may affect labor. The objective of this study was to determine if low PAPP-A is associated with labor dysfunction. METHODS: Retrospective study of pregnant women between July 2013 and July 2016. Women with PAPP-A in the 5 percentile were compared to women with PAPP-A ⩽1 percentile. Primary outcome: cesarean delivery (CD) rate. Secondary outcomes: indication for CD, perinatal outcomes. Exclusion: women with fetuses with known or suspected aneuploidy. RESULTS: One hundred thirty-nine women were included; 91 women with PAPP-A in 5 percentile and 48 women with PAPP-A ⩽1 percentile. Demographics were similar except for gestational age at delivery (38.6±3.6 weeks in the 5 percentile group versus 35.9±7.4 in the 1 percentile group, P =.004). There was no difference in CD rate (27/91 [29.7%] versus 12/48 [25%], P =.6), fetal indication for CD (8/27 [29.6%] versus 4/12 [33.3%], P =.8). Birth weight was significantly higher in the 5 percentile group versus the 1 percentile group (3, 264.6±580.8 versus 2, 935.4±715.3, P =.004). Neonatal morbidity composite score was different between groups; (18/91 [19.8%] in the 5 percentile group versus 18/48 [37.5%] in the 1 percentile group P =.02). CONCLUSION: PAPP-A ⩽1 percentile does not seem associated with delivery mode or indication for cesarean delivery in comparison to <5 percentile. PAPP-A ⩽1 percentile may be associated with increased neonatal morbidity during labor, as well as lower birth weight and preterm birth in comparison to PAPP-A <5 percentile.